2020
DOI: 10.1186/s12864-020-06837-y
|View full text |Cite
|
Sign up to set email alerts
|

Protein acetylation in mitochondria plays critical functions in the pathogenesis of fatty liver disease

Abstract: Background: Fatty liver is a high incidence of perinatal disease in dairy cows caused by negative energy balance, which seriously threatens the postpartum health and milk production. It has been reported that lysine acetylation plays an important role in substance and energy metabolism. Predictably, most metabolic processes in the liver, as a vital metabolic organ, are subjected to acetylation. Comparative acetylome study were used to quantify the hepatic tissues from the severe fatty liver group and normal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…It implied that the KATs and KDACs could alter biological functions of certain proteins to adapt the physiological changes by selectively modifying different substrates and acetylated sites of the proteins. In addition, we found that (G)K, K(H), and K(Y) were the favorable Kac sites, which are confirmed by other related acetyl-proteome studies on liver (27,48,49). Further analysis of the secondary structure of the protein between acetylated and unacetylated regions revealed that, in agreement with previous findings, Kac sites were usually located in the conservatively ordered secondary structure (49), which might result in a greater chromatin opening, thus facilitating transcriptional progression (50).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It implied that the KATs and KDACs could alter biological functions of certain proteins to adapt the physiological changes by selectively modifying different substrates and acetylated sites of the proteins. In addition, we found that (G)K, K(H), and K(Y) were the favorable Kac sites, which are confirmed by other related acetyl-proteome studies on liver (27,48,49). Further analysis of the secondary structure of the protein between acetylated and unacetylated regions revealed that, in agreement with previous findings, Kac sites were usually located in the conservatively ordered secondary structure (49), which might result in a greater chromatin opening, thus facilitating transcriptional progression (50).…”
Section: Discussionsupporting
confidence: 87%
“…Reduced acetylation of Rptor, which is a component of the mechanistic target of rapamycin kinase (Mtor) complex 1 and a key regulator of autophagy, protects mice from hepatic steatosis induced by starvation or high-fat diet (HFD) via induction of lipophagy ( 26 ). In addition, protein acetylation in mitochondria associates with important biological pathways involved in the regulation of the pathogenesis of fatty liver disease in dairy cows ( 27 ). These studies suggest that non-histone acetylation plays an important role in the regulation of liver lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that HMGCS2 activity is regulated, negatively by acetylation [ 91 ] and positively by phosphorylation [ 92 ]. HMGCS2 is also found to be highly acetylated in fatty livers [ 93 ]. Thus, it is plausible that ectopic HMGCS2 is catalytically more active with less acetylation, whereas long-term HFD feeding acetylates endogenous mouse Hmgcs2, making it less active.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction, trypsin digestion, LC-MS (MS/MS) analysis, and the database search were performed with reference to previously reported methods [68][69][70][71][72][73][74], with some modifications. The sample was ground into a cell powder in liquid nitrogen.…”
Section: Protein Extractionmentioning
confidence: 99%